German Bight estuaries: An inter-comparison on the basis of numerical modeling. (15th February 2019) - Stanev, Emil V.; Jacob, Benjamin; Pein, Johannes
Abstract: The Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM), which is an unstructured-grid model, was coupled with a 3D sediment model and established for the German Bight and its estuaries. The horizontal resolution of the model ranges from ~10 m in the estuaries to ~400 m in most of the open sea. Validation against tidal gauge data, fixed station data, and FerryBox data demonstrated that the model adequately simulated tidal dynamics in the entire area as well as the salinity fronts and estuarine turbidity maxima in the Ems, Weser and Elbe estuaries. Comparisons of model output with that of experiments with constant density allowed to estimate the role of density control, which appeared to be strongest in the landward reaches of salinity front. The increase of tidal range caused by density effects was most prominent in the Weser and Elbe estuaries, and relatively small in the Ems, where the runoff was also small. The magnitude of the density effect on the sea level oscillations was comparable to that of the M4 tide amplitude, demonstrating its importance in shaping the tidal asymmetry in the estuaries. Density effects not only reduced the dissipation of tidal energy; density stratification suppressed also the resuspension of sediment and contributed to a displacement of the position of the estuarine turbidity maximum upstream compared to the case of an homogeneous estuary. In the case of hyper-turbid Ems Estuary, density effects on stratification caused by high sediment concentrations resulted in a suppression of turbulence and further increase of concentration of suspended matter at the bottom. Although the three estuaries, which are only ~100 km apart, were driven by similar tidal and atmospheric forcings, they exhibited different extensions of both fronts and vertical stratification, mainly due to different river runoff conditions. At intra-tidal time scales, the dependencies between sea surface height and sea surface salinity varied considerably from estuary to estuary, and the largest flood asymmetry appeared in the Elbe Estuary. Wind acted as the dominant factor driving the longer-term estuarine variability; the correlation between zonal wind magnitude and sea surface height appeared to be very strong. The simulated suspended particulate matter dynamics and position of the estuarine turbidity maxima (ETM) were in agreement with observations. Secondary ETM appeared at different locations depending on the grain size, providing an illustration of sediment sorting. Highlights: SCHISM adequately simulates tidal dynamics in the German Bight and its estuaries. Density controls the tidal range, tidal asymmetry and position of estuarine turbidity maximum. Maximum concentration of SPM appear at different locations depending on the grain size. Wind and runoff are the dominant drivers of synoptic and longer-term estuarine variability. Although close to each other, the three estuaries exhibit different estuarine circulation.